Tissue and cell clinical use : an essential guide - Warwick, Ruth M.; Brubaker, Scott A. (Wiley, 2012)
This new book explores clinical information in the tissue transplantation field and acts as a comprehensive learning tool to comply with regulatory requirements. Broad in scope, coverage includes all the traditionally transplanted tissues and moves into more complex areas of tissue grafting and the assisted reproduction fields. This useful text focuses on the potential for disease transmission, ways to improve safety, and the role of the clinician in these safety aspects. The book starts off by describing non-surgical risks of using allografts and moves onto chapters devoted completely to tiss.